Measuring violence against women amidst war and displacement in northern Uganda using the "neighbourhood method". Issue 12 (24th November 2009) - Stark, L; Roberts, L; Wheaton, W; Acham, A; Boothby, N; Ager, A
Abstract : Background: Gender-based violence is viewed as a significant problem in conflict-affected regions throughout the world. However, humanitarian organizations typically have been unable to reliably estimate the incidence of rape, intimate partner violence and other forms of sexual abuse in such settings. Such estimates are required to inform programming in contexts such as northern Uganda. Methods: We sought to establish incidence rates for gender-based violence in internally-displaced-persons camps in northern Uganda. The assessments involved a "neighbourhood methodology, " in which adult female heads of household reported about their own, their sisters' and their neighbours' experiences. 299 households were selected for interview across four camps by using systematic random sampling. Findings: Interviews were completed by 204 respondents (5 women having declined interview and 90 not having been successfully contacted). These respondents reported on themselves, a total of 268 sisters and 1206 neighbours. Reports with respect to these alternative populations produced estimates of overall incidence of intimate partner violence in the past year of 51.7% (95% CI 44.8 to 58.7; respondents), 44.0% (95% CI 41.2 to 46.9; respondents' sisters) and 36.5% (95% CI 30.7 to 42.3; respondents' neighbours). In the same period, estimates of incidence of forced sex by husbands were 41.0% (95% CI 34.2% to 47.8%), 22.1% (95% CI 17.0 to 27.2) and 25.1% (95% CI 22.5 to 27.6), respectively, with incidence of rape by a perpetrator other than an intimate partner estimated at 5.0% (95% CI 2.0% to 8.0%), 4.2% (95% CI 1.8 to 6.6) and 4.3% (95% CI 3.1 to 5.5), respectively. Interpretation: Gender-based violence—particularly intimate partner violence—is commonplace in postconflict Uganda. The neighbourhood method provides a promising approach to estimating human right violations in humanitarian settings.